Deregulation of glutamate dehydrogenase in human neurologic disorders. Issue 8 (6th March 2013) - Plaitakis, Andreas; Zaganas, Ioannis; Spanaki, Cleanthe; Schousboe, Arne; McKenna, Mary C.
<x xml:space="preserve">Abstract</x> Mammalian glutamate dehydrogenase is an allosterically regulated enzyme that is central to glutamate metabolism. It contributes to important cellular processes, including Krebs cycle anaplerotic mechanisms, energy production, and ammonia homeostasis. In addition to this housekeeping hGDH1, humans have acquired through duplication an hGDH2 isoenzyme expressed in neural tissues with distinct regulatory properties. There is increasing evidence that deregulation of human GDHs leads to human disorders. Thus, in hGDH1, regulatory mutations that attenuate GTP inhibition can result in the hyperinsulinism/hyperammonemia syndrome, which is often associated with epileptic seizures, mental retardation, and generalized dystonia. Also, transgenic overexpression of GLUD1 in neurons has resulted in age‐dependent degeneration of the CA1 behippocampal region, associated with upregulation of α‐synuclein and other proteins linked to major human movement disorders. With regard to hGDH2, a rare T1492G variation in the GLUD2 gene, resulting in substitution of Ala for Ser445 in the regulatory domain of hGDH2, interacts significantly with Parkinson's disease (PD) onset. In two independent Greek and one North American PD cohorts, Ser445Ala hemizygous males, but not heterozygous females, developed PD 6–13 years earlier than subjects with other genotypes. The Ala445‐hGDH2 variant displays increased catalytic activity that is amenable to inhibition by estrogens. Enhanced glutamate oxidation by Ala445‐hGDH2 is thought to accelerate nigral cell degeneration in hemizygous males, and inhibition of the overactive variant by estrogens may protect heterozygous females. Hence, deregulation of hGDH1 and hGDH2 may play a role in degenerative processes, so these observations identify novel targets for therapeutic intervention in human disorders. © 2013 Wiley Periodicals, Inc.